PENGARUH PERENCANAAN PAJAK, ASET PAJAK TANGGUHAN DAN INTENSITAS MODAL TERHADAP MANAJEMEN LABA - Lastarina; Mu’arif, Syamsul (Jurnal Nusa Akuntansi, 2025)
This research aims to determine the influence of Tax Planning, Deferred Tax Assets and Capital Intensity on Profit Management in non-cyclical consumer companies for the 2018-2023 period. This type of research is quantitative research using secondary data obtained from the Indonesian Stock Exchange (BEI) and the analysis technique used in this research uses panel data regression analysis with the help of E-views version 12. This research was conducted on non-cyclical consumer companies. The data sampling technique used purposive sampling, the research samples were 24 companies with observations for 6 years 2018-2023. Based on the purposive sampling method, the total sample obtained was 144 data. The research results show that Tax Planning, Deferred Tax Assets and Capital Intensity simultaneously influence Profit Management. Partially, Tax Planning has a negative effect on Profit Management, Deferred Tax Assets and Capital Intensity have no effect on Profit Management.